The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/su8050421
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic EROI Assessment of the IPCC 21st Century Electricity Production Scenario

Abstract: Abstract:The Energy Return on Investment (EROI) is an important measure of the energy gain of an electrical power generating facility that is typically evaluated based on the life cycle energy balance of a single facility. The EROI concept can be extended to cover a collection of facilities that comprise a complete power system and used to assess the expansion and evolution of a power system as it transitions from one portfolio mix of technologies to another over time. In this study we develop a dynamic EROI m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Despite our dynamic approach significantly shortens the time step of the calculations (in the order of months), it represents still an average power over a certain time (which in conventional EROI studies corresponds with the lifetime of the technology). Hence, we decided to avoid the creation of a new term given that EROI is a concept widely used, and follow the terminology of ''dynamic EROI'' more commonly used in the literature 75,138,139 (although other more recent works have coined new terms such as ''power return on energy invested'' (PROI) 136,140 or ''net external power ratio'' (NEPR) 141,142 ). Still, it should be kept clear that the different nomenclature refers ultimately to the same concept.…”
Section: View Article Onlinementioning
confidence: 99%
“…Despite our dynamic approach significantly shortens the time step of the calculations (in the order of months), it represents still an average power over a certain time (which in conventional EROI studies corresponds with the lifetime of the technology). Hence, we decided to avoid the creation of a new term given that EROI is a concept widely used, and follow the terminology of ''dynamic EROI'' more commonly used in the literature 75,138,139 (although other more recent works have coined new terms such as ''power return on energy invested'' (PROI) 136,140 or ''net external power ratio'' (NEPR) 141,142 ). Still, it should be kept clear that the different nomenclature refers ultimately to the same concept.…”
Section: View Article Onlinementioning
confidence: 99%
“…4. a common reporting template to include the energy consumption of the energy sector as well as useful energy in mitigation scenarios; 8,201,202…”
Section: Avenues Of Improvement To Consider Net Energy In Iamsmentioning
confidence: 99%
“…A dynamic EROI assessment of the IPCC (Intergovernmental Panel on Climate Change) 21 st century electricity production scenario has been presented by Neumeyer and Goldston (2016). They observed that "the energy required to install and operate the infrastructure can be significant, especially at high rates of expansion, and has not been included explicitly in the overall IPCC scenario assessment".…”
Section: Net Energy Implications For Economic Growthmentioning
confidence: 99%